Handbook on social protection and social development in the Global South - Rapholo, Selelo F. (Social Work/Maatskaplike Werk, 2025)
This detailed yet useful volume fills a crucial gap in the scientific body of knowledge on social protection and social development, taking into consideration that many developing countries have recently been migrating from a residual approach to a development approach in addressing social problems and needs in society. The book situates social protection in a broader system of social welfare and development policies and programmes in the developing countries – the global South in particular. Each author in the book focused on a specific facet that is relevant to social protection and social development in the global South. This a very good and readable text that is well aligned with the Sustainable Development Goals (SGDs), for instance, SDG goal 1 on poverty reduction, which is integral to the achievement of the UN 2030 Agenda for Sustainable Development as it intersects with the other SDGs such as achieving zero hunger (SDG 2) and good health and well-being (SDG 3).